1984
DOI: 10.1007/bf00555204
|View full text |Cite
|
Sign up to set email alerts
|

Fluphenazine-induced acute and tardive dyskinesias in monkeys

Abstract: Five Cebus apella monkeys were treated with biweekly injections of fluphenazine enanthate (0.1-3.2 mg/kg IM). Three of these completed 1 full year of treatment, one injured its leg after 6 months of treatment and was killed, and another died of unknown causes after 9 months of treatment. All monkeys displayed abnormal movements corresponding to the early appearing extrapyramidal symptoms of neuroleptic-treated patients. These consisted initially of slowing or absence of volitional movement, trembling of the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Domino and Kovacic (1983), in fact, concluded that of 121 monkeys that have been given neuroleptics in several published studies, most developed only the acute dystonic or parkinsonism syndrome, and only 10 developed TD (some of those of Gunne and Barany, 1976;Bedard et al, 1977;McKinney et al, 1980). Kovacic and Domino (1984), Johansson (1989), and Gunne et al (1984) subsequently increased this sample, but the number of documented cases is clearly very low.…”
Section: Primate Studiesmentioning
confidence: 92%
“…Domino and Kovacic (1983), in fact, concluded that of 121 monkeys that have been given neuroleptics in several published studies, most developed only the acute dystonic or parkinsonism syndrome, and only 10 developed TD (some of those of Gunne and Barany, 1976;Bedard et al, 1977;McKinney et al, 1980). Kovacic and Domino (1984), Johansson (1989), and Gunne et al (1984) subsequently increased this sample, but the number of documented cases is clearly very low.…”
Section: Primate Studiesmentioning
confidence: 92%
“…These neurological side effects of neuroleptic drugs are troublesome and occasionally dangerous for patients. Similar syndromes are observed in monkeys treated with neuroleptics, including dystonic posturing of the face, trunk, and limbs, buccolinguo-masticatory movements (BLM), and a hyperactive state characterized by purposeless, restless movements resembling akathisia (AKA) (Gunne and Barany 1976;Bedard et al 1977;Meldrum et al 1977;Weiss et al 1977;Casey et al 1980;Liebman and Neale 1980;Porsolt and Jalfre 1981;Kovacic and Domino 1984). These behaviors typically evolve together over 'the course of repeated exposure to neuroleptics and Offprint requests to: D.E.…”
mentioning
confidence: 92%
“…[18][19][20] Challenged with a typical antipsychotic, this monkey readily develops syndromes similar to acute dyskinesia in humans. 18,19 Similarly, long-term treatment with neuroleptics leads to a chronic state resembling TD.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Challenged with a typical antipsychotic, this monkey readily develops syndromes similar to acute dyskinesia in humans. 18,19 Similarly, long-term treatment with neuroleptics leads to a chronic state resembling TD. [18][19][20] The acute effect of antipsychotics in C. apella previously sensitized to neuroleptics is predictive of the TD potential in humans and is generally assessed prior to initiating clinical trails.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation